Learning Speaking English on YouTube Videos: A Study on Students’ Perception - Yunnan Concesal; Roslaini Roslaini (Universitas Muhammadiyah Barru, 2024)
Media is essential to support learning activities, as they can capture the students’ attention when the learning process takes place. YouTube is one of the media that the students can pick anytime, especially for learning speaking. Therefore, the aim of this research is trying to explore the students’ perception on the use of YouTube Videos in learning speaking. This research uses a mixed-method design, and the data are collected using questionnaire and an interview. 30 students from public speaking course participated to fill out the questionnaire; 10 of them are interviewed to gain deeper information. After analysing the data using Likert Scale, the results shows that the students’ perception on the use of YouTube is significantly positive toward their learning. Based on the mean score, their opinion and interpretation about using YouTube videos are in good category or (4,22) and (4,13). From the interview, the result reinforces their exciting and enthusiasm in learning using YouTube videos. It means YouTube videos is favorable for learning particularly English speaking.